2023
DOI: 10.3390/ijms241512242
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Antiretroviral Therapy Dysregulates Iron Transport and Augments Mitochondrial Dysfunction in HIV-Infected Human Microglia and Neural-Lineage Cells

Harpreet Kaur,
Paige Minchella,
David Alvarez-Carbonell
et al.

Abstract: HIV-associated cognitive dysfunction during combination antiretroviral therapy (cART) involves mitochondrial dysfunction, but the impact of contemporary cART on chronic metabolic changes in the brain and in latent HIV infection is unclear. We interrogated mitochondrial function in a human microglia (hμglia) cell line harboring inducible HIV provirus and in SH-SY5Y cells after exposure to individual antiretroviral drugs or cART, using the MitoStress assay. cART-induced changes in protein expression, reactive ox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Chronic inflammation caused by beryllium is considered a possible contributor to the carcinogenicity of beryllium to humans ( 24 , 48 ). Currently, there is no research analyzing the synergistic effects of Cd and depression on PSA, and in an era where mental health has a significant impact, further research on the mechanisms and preventive measures is warranted ( 12 , 14 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation caused by beryllium is considered a possible contributor to the carcinogenicity of beryllium to humans ( 24 , 48 ). Currently, there is no research analyzing the synergistic effects of Cd and depression on PSA, and in an era where mental health has a significant impact, further research on the mechanisms and preventive measures is warranted ( 12 , 14 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…PBMCs from non-treated HIV-infected patients were found to have reduced CII, III, and IV activities [99]. We have recently shown in glial cells that the inhibitory effect of antiretrovirals on SDH is abrogated in the presence of latent or active HIV infection [100]. Effects of viral proteins on the ETC as a result of direct interaction have also been described.…”
Section: Viruses and Oxidative Phosphorylationmentioning
confidence: 98%
“…100 There are several NRTIs (eg, tenofovir, abacavir), NNRTIs (eg, efavirenz, rilpivirine, nevirapine), PIs (eg, atazanavir, darunavir, indinavir, ritonavir, saquinavir), and integrase strand transfer inhibitors (eg, dolutegravir, elvitegravir), which may be associated with mitochondrial dysfunction. 14 In general, studies have shown that combination ART can cause mitochondrial dysfunction in neurodegenerative disease states, 101 but studies in CVD remain more limited. The START trial (Strategic Timing of Antiretroviral Treatment) showed that, generally, CVD risk was insignificant between early or deferred ART, 102 suggesting that temporality is not principally governing the Mitochondria are the site of cellular respiration and ATP generation, as well as critical in the pathology of many diseases.…”
Section: Secondary Effects Of Hiv On Mitochondrial Function: the Impa...mentioning
confidence: 99%